Impact of Ki Hajar Dewantara's Leadership and Emotional Intelligence on Turnover Intention: The Mediating Effect Of Distributive Justice - Andri Purwanta; Syamsul Hadi; Kusuma Chandra Kirana (SMARTINDO, 2023)
Purpose - The rise of employee turnover intention in the organization will affect organizational performance and hinder the implementation of work programs. This study aims to analyze and empirically test the effect of Ki Hajar Dewantara's leadership trilogy and emotional intelligence on turnover intention mediated by distributive justice. Design/methodology/approach – The samples used amounted to 60 respondents with sample selection techniques using saturated sample techniques (census). This research is a quantitative study that uses questionnaires as the main data collection tool with a Likert scale. Data analysis methods using descriptive and inferential analysis, the analytical tool used is variance-based Partial Least Square (PLS) SEM, with SmartPLS V.4.0 software. PLS testing consists of indicator testing, model fit, hypothesis testing and mediation analysis. Conclusion – The results of this study indicate that the high level of Ki Hajar Dewantara's leadership and emotional intelligence does not affect the high level of turnover intention; Ki Hajar Dewantara's leadership trilogy and emotional intelligence have a significant positive effect on distributive justice; and distributive justice has a significant negative effect on turnover intention